Al-Falah Dalam Wakaf Tunai - Fatahuddin, Askar; Kara, Muslimin; Lutfi, Mukhtar; Abdullah, Wahyuddin (Jurnal Iqtisaduna, 2018)
Knowing the mechanisms in management of waqf management is very important to know both individuals and waqf institutions. The Indonesian Charity Foundation continues to make efforts to achieve maximum prosperity. However, what is the management if reviewed by fiqh, compilation of Islamic law and Law no. 4 of 2004 concerning representatives. This study uses a type of qualitative research with descriptive analysis and socio-historical approach to determine the observed organizational behavior. Exploration of the foundation’s programs, events, and activities was analyzed by a normative theological approach (fiqh, KHI) and the law to find out the implementation of cash waqf activities in a review of compilation of Islamic law and legislation on representation. Until finally it was discovered the management of cash waqf management, and knew the mechanism for the distribution of cash waqf management benefits based on the principles of "Giving", "Inspiring" and "Ikhlas" in establishing mauquf alaihi.